EFFECTIVE MORPHOLOGICAL AWARENESS INSTRUCTION FOR ENHANCING VOCABULARY ACQUISITION IN EFL STUDENTS: A STUDY AT AKM ISLAMIC SENIOR HIGH SCHOOL - Anggrisia, Nur Fitria; Billah, Ahmad Zulfahmi Muwafiq (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Vocabulary is a fundamental component of language expression, alongside speech and grammar. Effective communication in a second language (L2) requires a broad vocabulary, irrespective of students' proficiency in grammar and pronunciation. Preliminary observations at AKM Islamic Senior High School revealed many students have low vocabulary proficiency. Morphology, the study of word formation, includes affixation—adding or removing prefixes and suffixes. Morphological awareness, the ability to recognize and manipulate affixes, helps students deduce the meanings of unfamiliar words, thereby enriching their vocabulary. This study investigates the effectiveness of morphological awareness instruction in enhancing vocabulary among senior high school students. Using a true experimental design with a quantitative approach, participants were randomly selected by Mrs. F, an English teacher, and divided into experimental and control groups, each with 30 tenth-grade students. The experimental group received morphological instruction over three weeks, while the control group received traditional instruction using descriptive text material. Post-tests were administered to both groups, and data were analyzed using SPSS.25. The findings show a significant improvement in the experimental group's vocabulary proficiency, with an average post-test score of 68.40 compared to the control group's 53.80. An independent t-test confirmed a significant difference between the two groups. These results indicate that morphological awareness instruction is effective in improving the English vocabulary skills of senior high school students at AKM Islamic Senior High School.